Osmoadaptative Strategy and Its Molecular Signature in Obligately Halophilic Heterotrophic Protists. (12th July 2016) - Harding, Tommy; Brown, Matthew W.; Simpson, Alastair G.B.; Roger, Andrew J.
Abstract: Halophilic microbes living in hypersaline environments must counteract the detrimental effects of low water activity and salt interference. Some halophilic prokaryotes equilibrate their intracellular osmotic strength with the extracellular milieu by importing inorganic solutes, mainly potassium. These "salt-in" organisms characteristically have proteins that are highly enriched with acidic and hydrophilic residues. In contrast, "salt-out" halophiles accumulate large amounts of organic solutes like amino acids, sugars and polyols, and lack a strong signature of halophilicity in the amino acid composition of cytoplasmic proteins. Studies to date have examined halophilic prokaryotes, yeasts, or algae, thus virtually nothing is known about the molecular adaptations of the other eukaryotic microbes, that is, heterotrophic protists (protozoa), that also thrive in hypersaline habitats. We conducted transcriptomic investigations to unravel the molecular adaptations of two obligately halophilic protists, Halocafeteria seosinensis and Pharyngomonas kirbyi . Their predicted cytoplasmic proteomes showed increased hydrophilicity compared with marine protists. Furthermore, analysis of reconstructed ancestral sequences suggested that, relative to mesophiles, proteins in halophilic protists have undergone fewer substitutions from hydrophilic to hydrophobic residues since divergence from their closest relatives. These results suggest that these halophilic protists have a higher intracellular salt content than marine protists. However, absence of the acidic signature of salt-in microbes suggests that Haloc. seosinensis and P. kirbyi utilize organic osmolytes to maintain osmotic equilibrium. We detected increased expression of enzymes involved in synthesis and transport of organic osmolytes, namely hydroxyectoine and myo-inositol, at maximal salt concentration for growth in Haloc. seosinensis, suggesting possible candidates for these inferred organic osmolytes.